A View to the Future: A Novel Approach for 3D–3D Superimposition and Quantification of Differences for Identification from Next‐Generation Video Surveillance Systems1. Issue 2 (28th November 2016) - Gibelli, Daniele; De Angelis, Danilo; Poppa, Pasquale; Sforza, Chiarella; Cattaneo, Cristina
Abstract: Techniques of 2D–3D superimposition are widely used in cases of personal identification from video surveillance systems. However, the progressive improvement of 3D image acquisition technology will enable operators to perform also 3D–3D facial superimposition. This study aims at analyzing the possible applications of 3D–3D superimposition to personal identification, although from a theoretical point of view. Twenty subjects underwent a facial 3D scan by stereophotogrammetry twice at different time periods. Scans were superimposed two by two according to nine landmarks, and root‐mean‐square (RMS) value of point‐to‐point distances was calculated. When the two superimposed models belonged to the same individual, RMS value was 2.10 mm, while it was 4.47 mm in mismatches with a statistically significant difference ( p < 0.0001). This experiment shows the potential of 3D–3D superimposition: Further studies are needed to ascertain technical limits which may occur in practice and to improve methods useful in the forensic practice.